The Matthew Principle - Craig Howley (Arizona State University, 1995)
This study extends and interprets a regression technique used to examine the possible role that socioeconomic status may have in regulating the effects of school and district size on student achievement. The original study (Friedkin & Necochea, 1988), with data from California, confirmed an interaction between size and SES such that large schools benefitted affluent students, whereas small schools benefitted impoverished students. This replication applies the model to a very different state, West Virginia. Results are similar, except that the pattern of effects is shown to derive in part from the fact that in West Virginia impoverished students were shown actually to attend small schools in 1990. Small schools are shown to disrupt the usual negative relationship between socioeconomic status and student achievement. These results would be cause for celebration except that since 1988 West Virginia has, under a successful consolidation scheme facilitated by the state, closed nearly 20 percent of its schools, most of them small schools that had served rural communities in this mostly rural state. The discussion interprets findings with respect to this context and interprets the practical significance of studying structural variables such as those used in the study.